INTELLIGENT WILD ANIMAL SAFETY FENCE WITH REAL-TIME MONITORING AND ALERT SYSTEM - Ismail@Marzuki, M. S. N.; Samsolanuar, Z. S.; Wan Chek, W. A. K.; Mod Arifin, A. I.; Abu Bakar, H. H.; Mohd Zin, M. F. (Journal of Engineering and Technology (JET), 2026)
Human-wildlife conflict (HWC) poses risks to human safety, crops, and wildlife, especially in rural areas. This project proposes a Wild Animal Safety Fence, an automated IoT-based system to deter wildlife entry into restricted areas. Using PIR sensors and a Piezoelectric Accelerometer (SW-420) for motion and vibration detection, with an Arduino UNO R3 and NodeMCU (ESP8266), it sends real-time alerts via the Blynk app. Upon detection, a spotlight and alarm activate while notifying users. This system aims to protect humans and wildlife, offering a humane, cost-effective, and scalable solution by integrating IoT with conventional deterrents to manage HWC effectively.